The Anti-Influenza Virus Drug Favipiravir Has Little Effect on Replication of SARS-CoV-2 in Cultured Cells - Tomita, Yuriko; Takeda, Makoto; Matsuyama, Shutoku (Antimicrobial agents and chemotherapy, 2021)
Favipiravir (T-705, commercial name Avigan), a drug developed to treat influenza virus infection, has been used in some countries as an oral treatment for COVID-19; however, its clinical efficacy in this context is controversial.….